A new era in oxygen therapeutics? From perfluorocarbon systems to haemoglobin-based oxygen carriers. (July 2022) - Charbe, Nitin B.; Castillo, Francisco; Tambuwala, Murtaza M.; Prasher, Parteek; Chellappan, Dinesh Kumar; Carreño, Aurora; Satija, Saurabh; Singh, Sachin Kumar; Gulati, Monica; Dua, Kamal; González-Aramundiz, José Vicente; Zacconi, Flavia C.
Abstract: Blood transfusion is the key to life in case of traumatic emergencies, surgeries and in several pathological conditions. An important goal of whole blood or red blood cell transfusion is the fast delivery of oxygen to vital organs and restoration of circulation volume. Whole blood or red blood cell transfusion has several limitations. Free haemoglobin not only loses its tetrameric configuration and extracts via the kidney leading to nephrotoxicity but also scavenges nitric oxide (NO), leading to vasoconstriction and hypertension. PFC based formulations transport oxygen in vivo, the contribution in terms of clinical outcome is challenging. The oxygen-carrying capacity is not the only criterion for the successful development of haemoglobin-based oxygen carriers (HBOCs). This review is a bird's eye view on the present state of the PFCs and HBOCs in which we analyzed the current modifications made or which are underway in development, their promises, and hurdles in clinical implementation. Graphical abstract: The present state of potential oxygen carriers from perfluorocarbons to haemoglobin-based systems is presented where we analyzed the current modifications made or underway in its development, their promises, and hurdles in clinical implementation. Unlabelled Image